Measurement of Hazardous Pressure Levels and Gradients Produced on Human Limbs by Non-Pneumatic Tourniquets - McEwen, J.A.; Casey, V. (CMBES Proceedings, 2009)
This paper reports on existing and novel transducers for improved quantitative investigations of the levels of applied pressures and pressure gradients produced on human limbs by non-pneumatic tourniquet straps, and by non-pneumatic elastic bandages and elastic rolls when used as tourniquets, for comparison to benchmark data for pneumatic tourniquet cuffs commonly used in surgery at present.